2002
DOI: 10.1007/s00223-001-1088-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among VDR (BsmI and FokI), COLIA1, and CTR Polymorphisms with Bone Mass, Bone Turnover Markers, and Sex Hormones in Men

Abstract: Osteoporosis is a disease characterized by low bone mineral density (BMD) and up to 80% of its variance is under genetic control. Although osteoporosis is more frequent in women, one-third of hip fractures also occur in men. Much information on genetic factors and bone density has been obtained in women, but only a few studies have been performed in osteoporotic men. We have evaluated the relationship between polymorphisms for several candidate genes such as vitamin D receptor (VDR), collagen type Ia1 (COLIA1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
13

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 0 publications
1
23
0
13
Order By: Relevance
“…There is a large body of evidence relating the L447P of the CALCR to osteoporosis or bone fracture [9,10,11,12,13]. Recently the 3 ′ UTR+18C>T polymorphism has also been observed to be strongly associated with osteoporosis and bone fracture in a Korean population [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of evidence relating the L447P of the CALCR to osteoporosis or bone fracture [9,10,11,12,13]. Recently the 3 ′ UTR+18C>T polymorphism has also been observed to be strongly associated with osteoporosis and bone fracture in a Korean population [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some calcitonin receptor gene (CALCR) polymorphisms have been shown to be associated with bone mineral density in different populations [9,10,11,12,13]. Researchers have investigated the association of CALCR polymorphisms with urolithiasis, all identifying only a single nucleotide polymorphism (SNP) ( L447P polymorphism) [4,5,14], in which thymine (T) has been replaced by cytosine (C), causing a change from leucine to proline in the 447th amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies investigated the putative physiological relationship between circulating levels of 25OHD 3 /1,25(OH) 2 D, the activity of VDR and VD metabolizing enzymes, and serum testosterone and estradiol levels in both animals and humans (Tanaka et al 1976, Hyldstrup et al 1984, Small et al 1984, Hochberg et al 1985, Krabbe et al 1986, Sonnenberg et al 1986, Hagenfeldt et al 1992, Morley et al 1993, Inpanbutr et al 1996, Otremski et al 1997, Rapado et al 1999, Kinuta et al 2000, van Abel et al 2002, Braga et al 2002, Van Cromphaut et al 2003, Echchgadda et al 2004, Valimaki et al 2004, Kastelan et al 2009, Fleet & Schoch 2010, Krishnan et al 2010a, 2010b, Meng et al 2010, Pilz et al 2011, Ramlau-Hansen et al 2010, Wehr et al 2010, Ceglia et al 2011, Foresta et al 2011, Lundqvist et al 2011, Lee et al 2012. It has been shown that estrogen promotes the two-step activation of cholecalciferol to 1,25(OH) 2 D 3 and reinforces a positive effect on calcium homeostasis through a direct stimulatory effect on intestinal calcium absorption.…”
Section: Vd Regulates Biosynthesis Of Estradiol and Testosteronementioning
confidence: 99%
“…Studies in postmenopausal women revealed that the CC genotype is more common in non-osteoporotic women than the TT genotype [30,31], and that the TT genotype is associated with lower lumbar spine and femoral neck BMD and increases the predisposition for osteoporosis [32,33]. The opposite finding was suggested by Braga et al [34] who reported that the CC genotype is associated with decreased BMD and is more common in men with hip or vertebral fractures than in control subjects [34]. In our study, the CTR allele C together with a VDR C-A haplotype appeared to protect subjects from fractures.…”
Section: Discussionmentioning
confidence: 99%